CARCINO-SARCOMA 256 DE WALKER: DISSEMINACAO METASTATICA EM DUAS LINHAGENS DO TUMOR - de Mattos, M. C F I (My University, 1979)
Walker's 256 carcinoma changes its behaviour as a consequence of various factors. In this paper the authors compare the evolution of 2 lines of the tumor: WM 16 (muscular) and Christ Hospital (ascitic) both inoculated intramuscularly. Animals receiving line WM 16 had a severe rapidly progressive evolution dying around day 14 after inoculation with diffuse metastases to lymph nodes (65% of animals), kidneys (53%), spleen (50%), lungs (46.5%), liver (45%), bone marrow (44.8%), in 56% of the animals there were circulating tumoral cells. Animals receiving the Christ Hospital line survived up to 40 days, metastases were limited to lungs (48.7%) and lymph nodes (31.7%) and only in 2 of 45 animals circulating tumoral cells were observed.
Walker's 256 carcinosarcoma: Metastatic dissemination in two cell lines
Keywords: animal experiment; cell line; in vitro study; metastasis; rat; sarcoma; Animal; Carcinoma 256, Walker; Comparative Study; English Abstract; Lymphatic Metastasis; Male; Neoplasm Metastasis; Rats; Species Specificity